A política de assistência estudantil na Universidade Federal de Santa Maria: uma análise do auxílio à aquisição de material pedagógico - Perske, Ketlin Elís (2020)
The present work of the Professional Master's Course in Public Policies and Educational Management, of the Postgraduate Program in Public Policies and Educational Management, presents student assistance in higher education as the theme, in the context of the Dean of Student Affairs of the Federal University of Santa Maria (PRAE / UFSM). Its general objective is to define criteria and procedures contributing to qualify the actions of the Dean of Student Affairs in offering assistance for the acquisition of teaching material to undergraduate students at UFSM. And by specific objectives it recognizing in the history of Higher Education, its expansion, democratization and aspects related to student assistance in Brazil; analyze how student assistance policy and the assistance to the acquisition of pedagogical materials are offered and managed at the Federal University of Santa Maria; verify the perceptions of students and course coordinators regarding the aid of the acquisition of pedagogical material offered by PRAE/UFSM; develop criteria for the offer, grant and payment of the aid and from these, propose, as an educational product, a project for the computerization of the request for the aid in order to improve PRAE's actions.This is a qualitative research work based, of the case study type, carried out at UFSM. It was carried out on-campus with undergraduate students receiving assistance with the acquisition of teaching materials and with on-site undergraduate course coordinators. It was employed participant observation research techniques, documentary analysis and questionnaire. The theoretical framework is organized based on Morosini (2014), Vasconcelos (2010) and Dourado (2011) and content analysis was performed to understand the collected data. As result, it was concluded that student assistance at UFSM is fundamental for the permanence of students in socioeconomic vulnerability, coming from other cities and graduates of public schools, a number that is increasing every year. Housing and food are the actions most emphasized by participating students. For the assistance researched, the participants stressed that the amount of aid paid should be higher and that some modifications are necessary, such as the organization of a list of materials per course with on-line requests, as well as the other stages of the aid notice. The proposed educational product is a project to computerize the request for assistance for the acquisition of teaching material, via UFSM Student Portal, aiming (re) building more agile and secure request process, in order to improve the procedures involved at all stages of the assistance offer.